(untitled) (Journal of the College of Basic Education, 2022)
Ibrahim bin Al-Sheikh Muhammad bin Al-Husayn bin Muhammad HarajAl-Waeli is one of the poets who set out in the world of creativity in contemporary Iraqi poetry so it was a talent that set out in the sky of imagination creative linguistic structures and it is a dreamy artistic vision. To shed light on some aspects of artistic creativity in his poetry, which included three axes, the first axis was entitled [Dimensions of the Emotional Image in Ibrahim Al-Waeli’s Poetry] or the second axis, so it came under the title [The Political Image in Ibrahim Al-Waeli’s Poetry], while the title of the third axis [the symbol and its effect on shaping The image of Al-Waeli Technical].